System Hazard Analysis of Tower Crane in Different Phases on Construction Site - Ling Jiang; Tingsheng Zhao; Wei Zhang; Junjie Hu (Advances in Civil Engineering)
Tower crane accidents frequently occur in the construction industry, often resulting in casualties. The utilization of tower cranes involves multiple phases including installation, usage, climbing, and dismantling. Moreover, the hazards associated with the use of tower cranes can change and be propagated during phase alternation. However, past studies have paid less attention to the differences and hazard propagations between phases. In this research, these hazards are investigated during different construction phases. The propagation of hazards between phases is analyzed to develop appropriate safety management protocols according to each specific phase. Finally, measures are suggested to avoid an adverse impact between the phases. A combined method is also proposed to identify hazard propagation, which serves as a reference and contributes to safety management and accident prevention during different tower crane phases in the construction process.